Analisis Pengelolaan Modal Kerja terhadap Rasio Rentabilitas pada Perusahaan Manufaktur yang Terdaftar di BEI Periode Tahun 2018-2022 - Andi Harmoko Arifin (AKUNSIKA: Jurnal Akuntansi dan Keuangan, 2023)
The purpose of this research is to analyze the impact of working capital management on the improvement of profitability ratios in manufacturing companies listed on the Indonesian Stock Exchange during the period from 2018 to 2022. The population under investigation comprises all manufacturing companies listed on the Indonesian Stock Exchange during that period. In this study, a sample of 7 manufacturing companies listed on the IDX with complete financial reports was used, resulting in a total of 35 samples analyzed. The data analysis applied in this research involved hypothesis testing using the statistical software SPSS. The findings of this study indicate that working capital management is a critical element in a company's operations. It can be concluded that when a company is able to increase its sales volume, the resulting profit tends to increase, which subsequently has a positive impact on the company's profitability ratios. This underscores the importance of managing a company's current assets and current liabilities through working capital management to achieve high efficiency levels and ensure that net working capital is maintained at an acceptable level.